Quadruplexes in 'Dicty': crystal structure of a four-quartet G-quadruplex formed by G-rich motif found in the Dictyostelium discoideum genome - Guédin, Aurore; Lin, Linda Yingqi; Armane, Samir; Lacroix, Laurent; Mergny, Jean-Louis; Thore, Stéphane; Yatsunyk, Liliya A (Nucleic acids research, 2018)
Guanine-rich DNA has the potential to fold into non-canonical G-quadruplex (G4) structures. Analysis of the genome of the social amoeba Dictyostelium discoideum indicates a low number of sequences with G4-forming potential (249-1055). Therefore, D. discoideum is a perfect model organism to investigate the relationship between the presence of G4s and their biological functions. As a first step in this investigation, we crystallized the dGGGGGAGGGGTACAGGGGTACAGGGG sequence from the putative promoter region of two divergent genes in D. discoideum. According to the crystal structure, this sequence folds into a four-quartet intramolecular antiparallel G4 with two lateral and one diagonal loops. The G-quadruplex core is further stabilized by a G-C Watson-Crick base pair and a A-T-A triad and displays high thermal stability (Tm > 90°C at 100 mM KCl). Biophysical characterization of the native sequence and loop mutants suggests that the DNA adopts the same structure in solution and in crystalline form, and that loop interactions are important for the G4 stability but not for its folding. Four-tetrad G4 structures are sparse. Thus, our work advances understanding of the structural diversity of G-quadruplexes and yields coordinates for in silico drug screening programs and G4 predictive tools.
Keywords: nukleární magnetická rezonance biomolekulární; Nucleic Acid Conformation; Nuclear Magnetic Resonance, Biomolecular; Dictyostelium; G-kvadruplexy; cirkulární dichroismus; Mutation; spektrofotometrie ultrafialová; Genome; Promoter Regions, Genetic; G-Quadruplexes; Circular Dichroism; mutace; konformace nukleové kyseliny; krystalografie rentgenová; Crystallography, X-Ray; molekulární modely; genom; promotorové oblasti (genetika); Spectrophotometry, Ultraviolet; Models, Molecular